Accurate Nanoscale Crystallography in Real-Space Using Scanning Transmission Electron Microscopy. (14th July 2015) - Dycus, J. Houston; Harris, Joshua S.; Sang, Xiahan; Fancher, Chris M.; Findlay, Scott D.; Oni, Adedapo A.; Chan, Tsung-ta E.; Koch, Carl C.; Jones, Jacob L.; Allen, Leslie J.; Irving, Douglas L.; LeBeau, James M.
Abstract: Here, we report reproducible and accurate measurement of crystallographic parameters using scanning transmission electron microscopy. This is made possible by removing drift and residual scan distortion. We demonstrate real-space lattice parameter measurements with <0.1% error for complex-layered chalcogenides Bi2 Te3, Bi2 Se3, and a Bi2 Te2.7 Se0.3 nanostructured alloy. Pairing the technique with atomic resolution spectroscopy, we connect local structure with chemistry and bonding. Combining these results with density functional theory, we show that the incorporation of Se into Bi2 Te3 causes charge redistribution that anomalously increases the van der Waals gap between building blocks of the layered structure. The results show that atomic resolution imaging with electrons can accurately and robustly quantify crystallography at the nanoscale.